Reer Review: Dynamics Capital Sffuctue Of Firms In lndonesia Stock Exchange. - Dr. Arni Surwanti, M.Si. (Tamkang University, 2012)
Dynamics Capital Sffuctue Of Firms In lndonesia Stock Exchange. The 2012 Intermtional Conference in Managemen Sciencesand Decision Making tahun 2012 Tamkang University proceeding